Lipid formation and γ-linolenic acid production by Mucor circinelloides and Rhizopus sp., grown on vegetable oil - Tauk-Tornisielo, Sâmia M. [UNESP]; Arasato, Luciana S. [UNESP]; Almeida, Alex F. de [UNESP]; Govone, José S. [UNESP]; Malagutti, Eleni N. [UNESP] (Sociedade Brasileira de Microbiologia, 2009)
Linhagens de fungos foram testadas em sistema automatizado Bioscreen para selecionar melhor fonte nutricional. em seguida, foram estudadas culturas submersas em meios contendo uma única fonte de carbono e de nitrogênio. As linhagens contendo alta concentração de lipídeos tiveram melhor crescimento em meio contendo óleos de gergelim ou de dendê. Maior concentração de ácido γ-linolênico foi obtida com M. circinelloides nas culturas em óleo de gergelim.

The fungi strains were tested in Bioscreen automated system to select the best nutritional source. Following, shaking submserse cultures were studied in media containing sole carbon or nitrogen source. The growth of these strains improved in media containing vegetable oil, with high concentration of lipids. The high concentration of γ-linolenic acid was obtained with M. circinelloides in culture containing sesame oil.
Formação de lipídeos e produção de ácido γ-linolênico por Mucor circinelloides e Rhizopus sp., em óleos vegetais
Keywords: sistema automatizado de crescimento; óleos vegetais; zigomicetos; ácido γ-linolênico; ácido araquidônico; automated system; vegetable oils; zigomycetes; γ-linolenic acid; liquid culture